SCIENCE OF INFORMATICS AND INFORMATION TECHNOLOGIES SPECIFIC PRINCIPLES OF TEACHING - Turmanov, Kuatbay Amanbaevich (Educational Research in Universal Sciences, 2022)
The article talks about the content and uniqueness of teaching the science of informatics and information technology, the necessity of teaching this science today, and the problems in it. Recommendations on modern pedagogical technologies and methods used in teaching science are given.